2021
DOI: 10.3390/su13031340
|View full text |Cite
|
Sign up to set email alerts
|

Global Climate Pattern Impacts on Long-Term Olive Yields in Northwestern Africa: Case from Souss-Massa Region

Abstract: In arid to semi-arid regions, vulnerability to climate change combined with the overexploitation of water resources is jeopardizing food security. In the Souss-Massa region in central Morocco, the rural population relies on growing olives for a living. The management of these orchards is mostly traditional under rainfed irrigation, which induces a high level of dependence on climate variability. In the present study, we investigate the long-term trends of the relationship between the observed olive yields and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…In this study that determined the relationship between olive yield and El Nino and NAO in Turkey, no significant relationship was found with NAO, but significant relationship and low yield was found in strong El Nino years (Uzun and Ustaoğlu, 2019). Another study that found statistically significant relationships between olive yield and Nino 3.4 indicewas applied in Northwest Africa (Abahous et al, 2021). It has been determined that there are significant statistical relationships between olive yield and Nino 3.4 in Iran (Bannayan et al, 2011).…”
Section: Effects Of Extreme El Nino Phases On Crop Yieldsmentioning
confidence: 75%
See 1 more Smart Citation
“…In this study that determined the relationship between olive yield and El Nino and NAO in Turkey, no significant relationship was found with NAO, but significant relationship and low yield was found in strong El Nino years (Uzun and Ustaoğlu, 2019). Another study that found statistically significant relationships between olive yield and Nino 3.4 indicewas applied in Northwest Africa (Abahous et al, 2021). It has been determined that there are significant statistical relationships between olive yield and Nino 3.4 in Iran (Bannayan et al, 2011).…”
Section: Effects Of Extreme El Nino Phases On Crop Yieldsmentioning
confidence: 75%
“…This effect of atmospheric oscillations on climate is also observed directly on crops (Gimeno et al, 2002;Zubair 2002;Fraisse et al 2008;Soler et al 2010;Bannayan et al, 2011;Rao et al, 2011;Abdolrahimi, 2016;Capa. -Morocho et al, 2014;Iizumi et al, 2014;Gutierrez, 2017;Rojas et al, 2019;Uzun and Ustaoğlu, 2019;Qian et al, 2020;Abahous et al, 2021). Olive (Olea europaea L.) is a member of the maquis community included in the vegetation of the Mediterranean Climate.…”
Section: Introductionmentioning
confidence: 99%
“…In the study that determined the relationship between olive yield and El Nino and NAO in Turkey, no significant relationship was found with NAO, but significant relationship and low yield was found in strong El Nino years (Uzun & Ustaoğlu, 2019). Another study that found statistically significant relationships between olive yield and Nino 3.4 indicewas applied in Northwest Africa (Abahous et al, 2021). It has been determined that there are significant statistical relationships between olive yield and Nino 3.4 in Iran (Bannayan et al, 2011).…”
Section: Effects Of Extreme El Nino Phases On Crop Yieldsmentioning
confidence: 99%
“…This effect of atmospheric oscillations on climate is also observed directly on crops (Gimeno et al, 2002;Zubair 2002;Fraisse et al 2008;Soler et al 2010;Bannayan et al, 2011;Rao et al, 2011;Abdolrahimi, 2012;Capa. -Morocho et al, 2014;Iizumi 2014;Gutierrez, 2017;Rojas et al, 2019;Uzun & Ustaoğlu, 2019;Qian et al, 2020;Abahous et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…During the main cocoa purchase period, coinciding with the minor wet and major dry seasons, we observe increases in water deficit during El Niño, leading to drought stress conditions. In small-scale cocoa studies, drought stress is correlated with reduction in pod production and increased tree mortality 8,19 , and in similar studies of other tree crops drought is directly linked to reduction in fruit or nut production 20 , although in all cases the mechanisms are unclear. Drought may generally create unfavourable conditions for growth and reproduction through reduced availability of water for vital processes, or more specifically by promoting disease incidence and pod rot 8 , increasing the chance of fire, increasing competition for soil moisture 19 , and/or reducing pollinator populations 21 .…”
Section: Cocoa Crop Biologymentioning
confidence: 99%